Formation of Students’ Readiness for Using Computer Technologies at Music Lessons - Варнавська, Лариса Іванівна (Pedagogy of Higher and Secondary Education, 2013)
Varnavskaya L. I. Formation of Students’ Readiness for Using Computer Technologies at Music Lessons. The article analyses the issues of professional training, computer technologies usage at music lessons and the formation of students’ readiness to this type of activity; the meaning of «readiness for using the computer technologies at music lessons is defined concretely».